The empirical assessment of technology differences: comparing the comparable - Christoph M. Schmidt; Manuel Frondel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
This paper compares technologies across space and time on the basis of factual and counterfactual substitution elasticities and argues that differences in estimated substitution elasticities should be decomposed into two counterfactual components. While the first component is designed to indicate how the ease of substitution is altered by varied economic circumstances, the second addresses the question of how technologies would compare under genuinely comparable situations. This argument is illustrated by the example of energy-price elasticities of capital before and after the oil crisis of the early 1970s.
Keywords: C3; D2; 330; Counterfactuals; Substitutability; Translog Cost Function; Fertigungstechnik; Faktorsubstitution; Substitutionselastizität; Kostenfunktion; Schätzung; Erdölpreis; Preiselastizität; Deutschland; Kontrafaktische Situation